(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
Hydroclimatic data plays a crucial role in the study of water resources and the surrounding environment. These data are typically obtained from the National Water Agency and the state agencies. However, limited data series are available, and the data may contain undesirable characteristics. Data processing is usually performed using modules developed in spreadsheets; however, this method is impractical when dealing with large volumes of data. This led to the development of a Visual Basic for Applications (VBA) module in Microsoft Office Access to handle the extensive datasets. The application was designed to automatically process empty fields, clean invalid characters, and group data when large gaps appeared at the end of some tables. Finally, it calculated the monthly, daily, and annual averages. The application has proven to be highly intuitive because users only need to follow the sequence of buttons displayed on the screen.